Prophetic guidance training through the socratic method for MGBK in Pringsewu Regency - Santosa, Hardi; Prasetiawan, Hardi (Universitas Muhammadiyah Magelang, 2021)
Guidance and Counseling Teachers' Consultation (MGBK) is a community of teachers in the field of guidance and counseling. One of the main tasks of guidance and counseling teachers in schools is to guide students to become human beings with character as required by the National Education System Law No. 20 of 2003 concerning the complete goals of national education. However, not all guidance and counseling teachers have the competence to guard this goal. For this reason, guidance and counseling teachers need to be given training, so that they have adequate knowledge and skills in carrying out their duties. This training aims to increase the knowledge and skills of guidance and counseling teachers in implementing prophetic guidance. Prophetic guidance is designed with the aim of strengthening the character of students. The training method used socratic dialogue. The participants of the activity were 30 representatives from 30 high school, vocational, and MA schools in Pringsewu Regency, Lampung. The results of the training showed that 74% of participants stated that they really got the benefits and new knowledge, even as many as 61% of participants stated that they had increased their confidence. Thus, this service activity has a significant impact on improving the competence and performance of teachers in providing guidance and counseling services.